Diseño de un banco de pruebas hidráulico para actuadores lineales. - Rodriguez Polentino, Alexander; Prieto Quintero, David Felipe (Universidad Antonio Nariño, 2021)
This document develops the design of a prototype of a hydraulic bench that can be implemented to carry out internships at the university, an information search was carried out about the most common processes in the practices of hydraulic systems, and there were also some Recommendations such as the working pressure, which, because it is for university laboratory use, must be at pressures lower than those of the industrial level, also from the calculations made in which the components such as valves, cylinders and pumps that form can be determined. part of this hydraulic bench. As it is known, the university must seek every day to improve not only in the theoretical subject but in the practical one, which is why it was the reason that led us to carry it out.